ProNGF derived from rat sciatic nerves downregulates neurite elongation and axon specification in PC12 cells - Trigos, Anna S.; Longart, Marines; Garcia, Lisbeth; Castillo, Cecilia; Forsyth, Patricia; Medina, Rafael (Frontiers in Cellular Neuroscience, 2015)
Several reports have shown that a sciatic nerve conditioned media (CM) causes neuronal-like differentiation in PC12 cells. This differentiation is featured by neurite outgrowth, which are exclusively dendrites, without axon or sodium current induction. In previous studies, our group reported that the CM supplemented with a generic inhibitor for tyrosine kinase receptors (k252a) enhanced the CM-induced morphological differentiation upregulating neurite outgrowth, axonal formation and sodium current elicitation. Sodium currents were also induced by depletion of endogenous proNGF from the CM (pNGFd-CM). Given that sodium currents, neurite outgrowth and axon specification are important features of neuronal differentiation, in the current manuscript, first we investigated if proNGF was hindering the full PC12 cell neuronal-like differentiation. Second, we studied the effects of exogenous wild type (pNGFwt) and mutated (pNGFmut) proNGF isoforms over sodium currents and, whether or not their addition to the pNGFd-CM would prevent sodium current elicitation. Third, we investigated if proNGF was exerting its negative regulation through the sortilin receptor, and for this, the proNGF action was blocked with neurotensin (NT), a factor known to compete with proNGF for sortilin. Thereby, here we show that pNGFd-CM enhanced cell differentiation, cell proportion with long neurites, total neurite length, induced axonal formation and sodium current elicitation. Interestingly, treatment of PC12 cells with wild type or mutated proNGF isoforms elicited sodium currents. Supplementing pNGFd-CM with pNGFmut reduced 35% the sodium currents. On the other hand, pNGFd-CM+pNGFwt induced larger sodium currents than pNGFd-CM. Finally, treatments with CM supplemented with NT showed that sortilin was mediating proNGF negative regulation, since its blocking induced similar effects than the pNGFd-CM treatment. Altogether, our results suggest that proNGF within the CM, is one of the main inhibitors of full neuronal differentiation, acting through sortilin receptor.